Construction of healthy aging index from two different datasets - Miķelsone, Madara; Reine, Ieva; Tomsone, Signe; Guðmundsson, Helgi; Ivanovs, Andrejs; Guðmundsson, Halldór S. (Frontiers in Public Health, 2023)
The aging population presents both unique challenges and opportunities for societies around the world. Numerous attempts to quantify the aging process have been made. However, there is still a challenge in developing and choosing a good enough score that is easy to apply, has a construct of variables that are available in most nationwide surveys for comparable results, and at the same time reflects the aging process of older individuals. The purpose of this study is to present our approach to construct a comparable Healthy Aging Index (HAI). Material and methods: In Latvia, data from Wave 8 of the Survey of Health, Ageing and Retirement in Europe (SHARE), involving 420 respondents, was used. For comparative analysis, data from a HL20 study on the health and wellbeing of the elderly in Iceland, which included 1033 respondents, was used. Results: For Latvia, 13 items were selected, and for Iceland, nine items were selected. We constructed the HAI with four similar subscales for both countries -"Autonomy", "Health", "Wellbeing" and "Activities", and an additional subscale "Cognitive" for Latvia. Discussion: In our study, we found evidence for the successful construction of a HAI in two different datasets. The strength of our construct lies in the use of data from one of the largest social science panel studies in Europe (SHARE). As we were able to apply the construct to the Icelandic study, we believe that items presented in our approach are available in other population-based studies as well, and, therefore, can be easily replicated by others. By examining the existing SHARE data, HAI could be used to analyze long-term changes and could provide a foundation for comparing and monitoring the evolution of aging over time as well as comparing the aging process across societies. This is required for the authorities to conduct further analyses, proposals, and action plans in support of healthy aging.